Lung ultrasound characteristics in community-acquired pneumonia patients at Can Tho University of Medicine and Pharmacy Hospital - Hoang, Dang Nhat; Nghia, Phu Tri; Khoa, Vo Nhat; Bao, Nguyen The; Linh, Mai Thi Thuy; Tuan, Tran Trong Anh; Thu, Vo Pham Minh (Tạp chí Nghiên cứu Y học, 2026)
Semi-quantitative lung ultrasound has increasingly emerged as a bedside tool for evaluating pulmonary parenchymal involvement, yet evidence in community-acquired pneumonia remains limited. This analytical cross-sectional study investigated lung ultrasound features and their associations with selected severity assessment tools and inflammatory markers in 85 patients with community-acquired pneumonia admitted to the Department of General Internal Medicine, Can Tho University of Medicine and Pharmacy Hospital, from June 2025 to January 2026. The median age was 73.0 years old, and 55.3% were men. B-lines/lung rockets were the most common ultrasound finding (98.8%), followed by the shred sign (58.8%), air bronchograms (47.1%), and pleural effusion (17.6%). Consolidation with or without interstitial syndrome was the predominant lesion pattern (64.7%), whereas isolated interstitial syndrome accounted for 34.1%. Spline analysis showed that CRP and WBC increased with higher total lung ultrasound scores, with significant overall associations (p<0.001 and p=0.032, respectively). The total lung ultrasound score also increased progressively with pneumonia severity according to both CURB-65 and PSI/PORT (p<0.05). In multivariable analysis, CRP and severity assessed by CURB-65 and PSI/PORT were independently associated with the total lung ultrasound score. Lung ultrasound may therefore support assessment of inflammatory burden, severity stratification, follow-up, and prognostication in community-acquired pneumonia.